Scribble: Auto-Generated 2D Avatars with Diverse and Inclusive Art-Direction - Petikam, Lohit; Hewitt, Charlie; Rezaeifar, Shideh (SIGGRAPH, 2024)
Stylized avatars are a popular digital, graphical representation of unique users in teleconferencing, hybrid presence and gaming applications. As avatar systems become commonplace, there will be an increasing need to ensure that those systems support the wide range of appearance present in the human population. Existing human avatar systems typically use a single, generic base rig that morphs into varied human face and body shapes. It is costly to add extra anatomical shapes for under-represented human populations on top of a base rig originally designed for a majority demographic. This leaves many avatar systems struggling to catch up when it comes to fair representation of different demographics, especially for stylized avatars with limited visual language to depict diverse human attributes. We need new avatar systems, visual languages, and human understanding technologies that are co-designed with thoughtful consideration of diversity, right from the start.